Two New Spiro-Heterocyclic γ-Lactams from A Marine-Derived Aspergillus fumigatus Strain CUGBMF170049 - Xu, Xiuli (Mar Drugs, 2019)
Two new spiro-heterocyclic γ-lactam derivatives, cephalimysins M (1) and N (2), were isolated from the fermentation cultures of the marine-derived fungus Aspergillus fumigatus CUGBMF17018. Two known analogues, pseurotin A (3) and FD-838 (4), as well as four previously reported helvolic acid derivatives, 16-O-propionyl-16-O-deacetylhelvolic acid (5), 6-O-propionyl-6-O-deacetylhelvolic acid (6), helvolic acid (7), and 1,2-dihydrohelvolic acid (8) were also identified. One-dimensional (1D), two-dimensional (2D) NMR, HRMS, and circular dichroism spectral analysis characterized the structures of the isolated compounds.